Uji Distribusi Normal Multivariat dengan Kendala Mean Terurut - , DIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this thesis, the test ordered means of multivariate normal distribution against all alternatives for case when the covariance matrices are known. Use the likelihood ratio method and isotonic application, we obtain the test statistic and study its null distribution. to propose the critical values and simulation study for compute power of test and p-value from bivariate normal distribution.